If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = 5x + -1(5x + -1x)(5x + -1x) Combine like terms: 5x + -1x = 4x 100 = 5x + -1(4x)(5x + -1x) Remove parenthesis around (4x) 100 = 5x + -1 * 4x(5x + -1x) Combine like terms: 5x + -1x = 4x 100 = 5x + -1 * 4x(4x) Remove parenthesis around (4x) 100 = 5x + -1 * 4x * 4x Reorder the terms for easier multiplication: 100 = 5x + -1 * 4 * 4x * x Multiply -1 * 4 100 = 5x + -4 * 4x * x Multiply -4 * 4 100 = 5x + -16x * x Multiply x * x 100 = 5x + -16x2 Solving 100 = 5x + -16x2 Solving for variable 'x'. Reorder the terms: 100 + -5x + 16x2 = 5x + -5x + -16x2 + 16x2 Combine like terms: 5x + -5x = 0 100 + -5x + 16x2 = 0 + -16x2 + 16x2 100 + -5x + 16x2 = -16x2 + 16x2 Combine like terms: -16x2 + 16x2 = 0 100 + -5x + 16x2 = 0 Begin completing the square. Divide all terms by 16 the coefficient of the squared term: Divide each side by '16'. 6.25 + -0.3125x + x2 = 0 Move the constant term to the right: Add '-6.25' to each side of the equation. 6.25 + -0.3125x + -6.25 + x2 = 0 + -6.25 Reorder the terms: 6.25 + -6.25 + -0.3125x + x2 = 0 + -6.25 Combine like terms: 6.25 + -6.25 = 0.00 0.00 + -0.3125x + x2 = 0 + -6.25 -0.3125x + x2 = 0 + -6.25 Combine like terms: 0 + -6.25 = -6.25 -0.3125x + x2 = -6.25 The x term is -0.3125x. Take half its coefficient (-0.15625). Square it (0.0244140625) and add it to both sides. Add '0.0244140625' to each side of the equation. -0.3125x + 0.0244140625 + x2 = -6.25 + 0.0244140625 Reorder the terms: 0.0244140625 + -0.3125x + x2 = -6.25 + 0.0244140625 Combine like terms: -6.25 + 0.0244140625 = -6.2255859375 0.0244140625 + -0.3125x + x2 = -6.2255859375 Factor a perfect square on the left side: (x + -0.15625)(x + -0.15625) = -6.2255859375 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 4x^2+8=3x+15 | | 4x+1=20x | | 3xz-3xy=0 | | 10squared=5x-(5x-x)(5x-x) | | 0.05xa=5 | | 8d-4=12-14 | | 5sinx-12cosx-9=0 | | 7(p-8)=8p+35 | | (-1)a=-a | | R=H+4*20 | | 10+2x^3=7 | | 4*4x+7-5x=8+(-5)(5x-6x)+23 | | 3x+3(-2x)=x-3 | | 3(m+5)= | | 7(2x-1)=4x+3 | | g(x)=-3x^2+30x-77 | | 114=19y | | p^2(p^2-4)=3p^2+-8 | | 3*4x=35+5x | | 9w=5670 | | p^2(p^2-4)=3p^2-8 | | -16x^2+105x-34= | | 2*4x+4=28 | | -16x^2-105x-34= | | (5x-15)(2-x)=0 | | 10-4x=x-16-3x | | 9x+3=5x+3 | | 12=3-5k | | 9x-6x+3=7x-2x | | 2(3-x)=3(x+15) | | 21=5+33t-16t^2 | | 5x-9=2x+14 |